Species richness, geographic distribution and endemism of Pinguicula (Lentibulariaceae) in the Mexican Transition Zone - López-Pérez, Jorge David; Zamudio, Sergio; Munguía-Lino, Guadalupe; Rodríguez, Aarón (Phytotaxa, 2024)
The genus Pinguicula (Lentibulariaceae) is composed of 115 species of carnivorous plants and Mexico is a center of diversification. The Mexican Transition Zone (MTZ) is the boundary between the Nearctic and Neotropical regions. It includes the main mountain ranges of Mexico, which extend south to northeastern Nicaragua. Its geological history, physiographic diversity and climatic complexity would have provided the environment to support a rich flora as well as angiosperm endemism. It was expected that the distribution of Pinguicula would have the same pattern. To test this hypothesis, a database was constructed based on the review of herbaria specimens, digital herbaria, bibliography, and databases. Species richness distribution and endemism were evaluated by country, biome, biogeographic province, elevation gradient, and three grid-cells sizes. The species richness of Pinguicula was centered in Mexico in an elevation gradient extending from 1,501–2,000 m. Also, species richness was greatest in the Tropical & Subtropical Coniferous Forest biome. However, considering biogeographic criteria, the Sierra Madre Oriental (SMOr) was the richest province. This was also supported by the distribution of the cells with the highest species richness and endemism. The results showed that the pattern of species richness and endemism of Pinguicula was concentrated along the MTZ, particularly in the SMOr.